Bootstrapping the 3d Ising stress tensor - Cyuan-Han Chang; Vasiliy Dommes; Rajeev S. Erramilli; Alexandre Homrich; Petr Kravchuk; Aike Liu; Matthew S. Mitchell; David Poland; David Simmons-Duffin (Journal of High Energy Physics)
Abstract We compute observables of the critical 3d Ising model to high precision by applying the numerical conformal bootstrap to mixed correlators of the leading scalar operators σ and ϵ, and the stress tensor T μν . We obtain new precise determinations of scaling dimensions (∆ σ , ∆ ϵ ) = (0.518148806(24), 1.41262528(29)) as well as OPE coefficients involving σ, ϵ, and T μν . We also describe several improvements made along the way to algorithms and software tools for the numerical bootstrap.